2001
DOI: 10.1108/eum0000000005979
|View full text |Cite
|
Sign up to set email alerts
|

The use of human resource information systems: a survey

Abstract: Presents the results of a survey of the use of human resource information systems (HRIS) in smaller organizations, conducted in 1998. The survey enquires as to the nature of information stored electronically in three core areas: personnel, training and recruitment as well as the type of information analysis being undertaken. Significant relationships were found between the total number of people employed by the organization, and certain aspects of its information storage and manipulation. Smaller organizations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
158
0
7

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 203 publications
(171 citation statements)
references
References 18 publications
6
158
0
7
Order By: Relevance
“…While there are a range of competing definitions of HRIS (Ball, 2001;Hyde & Shafritz, 1977;Kavanagh & Thite, 2009), there is general consensus that a HRIS is a system used to acquire, store, analyze, retrieve and distribute pertinent information regarding an organization's human resources (Bondarouk & Ruël, 2008;Hendrickson, 2003) and that it includes hardware, software, people, policies, procedures, and data (Kavanagh, Gueutal, & Tannenbaum, 1990). The study of HRIS can be regarded as a distinct area of research within the e-HRM domain Strohmeier, 2007;Voermans & Van Veldhoven, 2007).…”
Section: The Paradox Of Hris: Hris In the Human Resource Management Lmentioning
confidence: 99%
“…While there are a range of competing definitions of HRIS (Ball, 2001;Hyde & Shafritz, 1977;Kavanagh & Thite, 2009), there is general consensus that a HRIS is a system used to acquire, store, analyze, retrieve and distribute pertinent information regarding an organization's human resources (Bondarouk & Ruël, 2008;Hendrickson, 2003) and that it includes hardware, software, people, policies, procedures, and data (Kavanagh, Gueutal, & Tannenbaum, 1990). The study of HRIS can be regarded as a distinct area of research within the e-HRM domain Strohmeier, 2007;Voermans & Van Veldhoven, 2007).…”
Section: The Paradox Of Hris: Hris In the Human Resource Management Lmentioning
confidence: 99%
“…This practice reduces the use of papers for each of the supervisor and oversight which can minimize the time and cost of striking to the Human Resources Department. Self-service applications allow managers to instantly enter the results of performance appraisal management, employee's performance goals, results and performance planning on their personal pages HR (Ball, 2001). …”
Section: E-performancementioning
confidence: 99%
“…Kovach and Cathcart (1999) noted that an HRIS need not be computerised since the main goal of information is to allow quicker decisions. The first forms of true HRIS were payroll systems created during the 1960s (Ball, 2001). Since then, these systems have come to be used widely throughout many organisations (DeSanctis, 1986;Kossek et al, 1994).…”
Section: Literature Reviewmentioning
confidence: 99%
“…One study found in 1996 that the previous 10-15 years had found major changes in the technology of such systems (Groe et al, 1996). Another paper found that while the systems and their impacts have been studied, very little of those studies examined the technology used by HRIS and its impact on HRM (Ball, 2001). Bondarouk and Ruël (2009) noted that research on the field seems to have stalled or is simply duplicating itself and instead believe that the focus should be on the consequences to entire organisations when HR systems are implemented, taking a larger view of the field.…”
Section: Literature Reviewmentioning
confidence: 99%